Plasmacytoma of the iliac bone in a seven- year-old girl: A rare tumor with no to ignore - Lohourou Grah Franck; Kpangni Ahua Jean Bertrand; Bénie Abdous Célestin; Traoré Ibrahim; Touré Ibrahiman; Bony Constance; N'Da-Koffi Cinthia (Elsevier, 2021)
Solitary bone plasmacytoma is a rare plasmocytic neoplasm accounting for about 5% of all plasmocytic neoplasms. It is usually presented as a lytic lesion mainly localized in the axial skeleton. Its presence in adolescents is extremely rare. It is unheard of in children. We report a case of solitary plasmacytoma of the iliac bone in a 7-year-old girl with a history of trauma to the iliac bone.